The Effort to Rationalize Antibiotic Use in Indonesian Hospitals: Practice and Its Implication. (25th February 2023) - Siahaan, Selma; Rukmini, Rukmini; Roosihermiatie, Betty; Andarwati, Pramita; Handayani, Rini S.; Tarigan, Ingan U.; Rosita, Tita; Rustika, Rustika; Usman, Yuslely; Kristiana, Lusi
Abstract : An effective strategy for combatting AMR in Indonesia is to make the use of antibiotics in hospitals more rational with the help of an Antimicrobial Resistance Control Program (AMR-CP). This study aims to analyze the implementation of the AMR-CP in hospitals by conducting in-depth interviews with health professionals from ten hospitals and health officers of ten provincial health offices in ten different provinces and observation towards its documents. The sample location was selected by purposive sampling. Informants at the hospitals were hospital directors, chairmen of the AMR-CP team, chairmen of the medical committee, persons in charge of the microbiology laboratory, clinicians, nurses, clinical pharmacists, and those program managers at the provincial health offices who are responsible for administering antibiotics. Information is first collected and then a thematic analysis is applied along with triangulation to confirm the validity of information from multiple sources, including document observation results. The analysis is adapted to the framework of the system (i.e., input, process, and output). Results show that hospitals in Indonesia already have the resources to implement AMR-CP, including AMR-CP team and microbiology laboratories. Six hospitals examined also have clinicians trained in microbiology. Though hospital leadership and its commitment to implementing AMR-CP are favorable, there is room for improvement. AMR-CP teams organize routine activities for socialization and training, develop standard operating procedures (SOPs) for antibiotic use, antibiotic patterns surveillance, and bacterial mapping. Some obstacles to implementing AMR-CP policies are posed by the human resources, facilities, budget, antibiotics and reagent shortages, and clinician compliance with SOPs. The study concludes that there was an improvement in antibiotic sensitivity patterns, rational use of antibiotics, use of microbiological laboratories, and cost-efficiency. It recommends the government and healthcare providers continue to improve AMR-CP in hospitals and promote AMR-CP policy by making the regional health office of the hospital a representative of the regional government.